Mass spectrometry‐based method for quantification of nimodipine and glutamate in cerebrospinal fluid: pilot study with patients after aneurysmal subarachnoid haemorrhage - Mindt, Sonani; Tokhi, Ursala; Hedtke, Maren; Groß, Hans-Jürgen; Hänggi, Daniel (Journal of clinical pharmacy and therapeutics, 2020)
This study describes the range of nimodipine and glutamate values in CSF following aSAH. Technical aspects for nimodpine and glutamate measurement in CSF using a developed LC/MS/MS method.
First published: 17 August 2019
Gesehen am 26.01.2021